1. Contents - Redakcja (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 1994)
This volume takes up the controversial problems of the early agrarian stage of „pastoral cultures”. It contains the contribution of authors who are united in their conviction of the need to analyze the „classical” interpretation, which is of a monolinear, very dynamic development of the East European pastoralism and its Central European (or — to use a wider term — West European) manifestations. All articles were created under the Editor’s authorization and they concern a special register of questions. The questions addressed are: genesis and changes of the given phenomena, functional requalification of economic and social systems, traditionally considered to be „pastoral” ones; as well as the reconstruction of fields of culture, considered to be particularly useful in analyzing the development of the civilizational trend (metallurgy, weapons), in which we are interested. The volume does not exhaust all the necessary aspects of the discussion. I hope that we will be able, in the near future, to present its continuation within the Baltic-Pontic Studies. 1. All dates in the B-PS are calibrated [see: Radiocarbon vol.28, 1986, and the next volumes]. Deviations from this rule will be point out in notes. 2. The names of the archaeological cultures (especially from the territory of the Ukraine) are standarized according to the English literature on the subject [e.g. Mallory 1989]. In the case of a new term, the author’s original name has been retained. 3. The place names located in the Ukraine have been transliterat from the ver¬sions suggested by the author (i.e. from the Ukrainian, Polish or Russian originals).